Metaheuristic optimization in power engineering - Radosavljević, Jordan (The Institution of Engineering and Technology, 2018)
This book describes the principles of solving various problems in power engineering via the application of selected metaheuristic optimization methods including genetic algorithms, particle swarm optimization, and the gravitational search algorithm.
Keywords: Power resources -- Mathematical models.; Energy industries -- Mathematical models.; Mathematical optimization.; Engineering mathematics.; elektronické knihy; electronic books